2022
DOI: 10.1093/noajnl/vdac067
|View full text |Cite
|
Sign up to set email alerts
|

IDH-mutant astrocytoma with EGFR amplification—Genomic profiling in four cases and review of literature

Abstract: EGFR amplification is associated with aggressive glioma behavior and regarded as a molecular feature of glioblastoma. Although rare, IDH-mutant astrocytomas with EGFR amplification exist but remain poorly understood. We report the clinical and molecular profile of four grade 4 IDH-mutant astrocytomas with EGFR amplification, evaluated using histology, DNA sequencing, cytogenetics, and DNA methylation profiling. Other alterations included ATRX, TP53, and PIK3CA mutations; CDKN2A/B loss; PDGFRA+KIT amplification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Notably, these new prognostic features did not reach statistical significance in the TCGA cohort, highlighting the population heterogeneity between non-TCGA and TCGA cohorts. 3638 Moreover, we observed that being of white race emerged as a favorable prognostic indicator for IDH1/2 -mutant astrocytomas. This finding raises concerns about structural disparities in access to timely surgical and medical care or clinical trial enrollment, which may affect treatment outcomes.…”
Section: Discussionmentioning
confidence: 68%
“…Notably, these new prognostic features did not reach statistical significance in the TCGA cohort, highlighting the population heterogeneity between non-TCGA and TCGA cohorts. 3638 Moreover, we observed that being of white race emerged as a favorable prognostic indicator for IDH1/2 -mutant astrocytomas. This finding raises concerns about structural disparities in access to timely surgical and medical care or clinical trial enrollment, which may affect treatment outcomes.…”
Section: Discussionmentioning
confidence: 68%
“…Alterations in the receptor tyrosine kinase EGFR occur frequently in IDH wild-type glioma but are rarely reported in IDH-mutant tumors 24 , 25 . Upon examination of four IDH-mutant tumors with NE and CE samples available (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of EGFR Amp was seldom depicted in IDH-mutant diffuse gliomas. Several previous studies included IDH-mutant GBM which is defined as IDH-mutant astrocytoma (WHO grade 4) currently, and examined EGFR Amp, with the ratio ranging from 3% to 16% ( Verhaak et al, 2010 ; Brennan et al, 2013 ; Li et al, 2019 ; Wong et al, 2021 ; Umphlett et al, 2022 ). Besides, a study by Bai et al found that 16 out of 86 (18%) IDH-mutant grade 2 to 3 gliomas were EGFR -amplified ( Bai et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prognostic role of EGFR Amp in the new entity of GBM under the 2021 WHO criteria needs further investigation. On the contrary, in IDH-mutant gliomas, EGFR alterations were less common and its prognostic value was under evaluated ( Bai et al, 2016 ; Umphlett et al, 2022 ). A study by Craig Horbinski et al used EGFR immunohistochemistry (IHC) and showed that EGFR expression failed to discriminate survival among astrocytic tumors ( Horbinski et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%